2010
DOI: 10.4067/s0717-95022010000100028
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Branching Pattern of the Celiac Trunk in a Kenyan Population

Abstract: SUMMARY:The celiac trunk is the major source of blood supply to the supracolic abdominal compartment. Usually, it branches into the splenic, common hepatic and left gastric arteries to supply this region. It has however been shown to display ethnic variations in its branching pattern. Knowledge of these variations may be important in surgical and radiological procedures around the head of the pancreas. The aim was to illustrate the commonest variations in the branching pattern of the celiac trunk in a Kenyan p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 21 publications
(17 reference statements)
3
37
2
1
Order By: Relevance
“…IJBAR (2014) 05 (10) www.ssjournals.com The hepatosplenic trunk (Type II) and separate LGA from the aorta have been reported in the literature 10,[13][14][15][16]18,21,22,36,37 . The LGA commonly arises from the CT as one element of its trifurcation.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…IJBAR (2014) 05 (10) www.ssjournals.com The hepatosplenic trunk (Type II) and separate LGA from the aorta have been reported in the literature 10,[13][14][15][16]18,21,22,36,37 . The LGA commonly arises from the CT as one element of its trifurcation.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
“…Mburu studied 123 specimens and observed the origin of IPA from the CT in 4.9% 15 . The previous study conducted by Tiwari 20 and Petrella 25 showed the origin of RIPA alone from the CT in 2% and 5.62%, LIPA alone in 4% and 21.35%, whereas both IPAs in 4% and 7.86% respectively.…”
Section: Review Of Literature and Discussionmentioning
confidence: 99%
See 3 more Smart Citations